2022
DOI: 10.4102/phcfm.v14i1.3668
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported knowledge and skills related to diagnosis and management of keratoconus among public sector optometrists in the Limpopo province, South Africa

Abstract: Background: Keratoconus (KC) has been regarded as a rare condition, although recent studies, including those in South Africa, suggest it is common and is increasing in prevalence. Furthermore, South African-based studies have shown that KC is normally detected at advanced or severe stages. Knowledge and skills for examination, diagnosis and management of KC by optometrists are important for the early detection and management of the disease.Aim: This study aimed to evaluate self-reported knowledge and skills fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Other African countries such as South Africa and Ghana have reported similar results regarding poor access to corneal topographers. 15 , 16 , 28 There is therefore a need for African universities to initiate innovations to design cost-effective corneal topographers to improve the diagnosis and management of KC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other African countries such as South Africa and Ghana have reported similar results regarding poor access to corneal topographers. 15 , 16 , 28 There is therefore a need for African universities to initiate innovations to design cost-effective corneal topographers to improve the diagnosis and management of KC.…”
Section: Discussionmentioning
confidence: 99%
“…Half the number of optometrists had access to and were confident in performing keratometry, this being similar to reports from South Africa and Ghana. 15 , 16 , 28 Despite keratometry measurements being limited to the central 3 to 4mm of the cornea and the cone in KC decentering as it progresses, 29 keratometers are cost-effective with good repeatability up to K-readings of 55D. 30 In the absence of corneal topographers practitioners should, at the least, use the keratometer, combined with other clinical signs such as a split/scissor retinoscopy reflex and/or astigmatism of >2.00DC and/or slit lamp signs of KC to screen and monitor for progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have previously examined keratoconus management and referral patterns for community optometrists. 8,[10][11][12] A previous study of 71 optometrists, completed in New South Wales, Australia, identified barriers to prescribing RGP lenses and criteria for referring patients for ophthalmological assessment and further management. 8 This study sought to assess the diagnostic, referral, and therapeutic management of optometrists in New Zealand and investigate possible mechanisms to support primary care to achieve the best outcomes for patients with keratoconus.…”
mentioning
confidence: 99%
“…Few studies have previously examined keratoconus management and referral patterns for community optometrists. 8,10–12 A previous study of 71 optometrists, completed in New South Wales, Australia, identified barriers to prescribing RGP lenses and criteria for referring patients for ophthalmological assessment and further management. 8…”
mentioning
confidence: 99%